A Twisted Tale of Vein of Galen Aneurysmal Malformation - Sanghani, Rohit; Panchal, Toral (Journal of Fetal Medicine, 2024)
This illustration presents a three-dimensional representation of the vascular structure of the vein of Galen aneurysmal malformation (VGAM), which is a rare congenital brain vascular abnormality characterized by the enlargement of the embryonic precursor of the vein of Galen—specifically, the median prosencephalic vein of Markowski. VGAM constitutes an arteriovenous fistula formed between the deep choroidal arteries and the embryonic median prosencephalic vein. Its development initiates early but is typically detectable via sonography only during the second- or third-trimester of gestation. The comprehensive assessment of the vascular anatomy of VGAM necessitates the examination of both the incoming (afferent) and outgoing (efferent) vessels.
Keywords: Vein of Galen Aneurysmal Malformation; Congenital anomaly; Vascular malformation